Flow Simulation and Energy Loss Estimation in the Nappe Flow Regime of Stepped Spillways with Inclined Steps and End Sill: A Numerical Approach - Amirmasoud Hamedi; Mohammad Hajigholizadeh; Abbas Mansoori (Salehan Institute of Higher Education, 2016)
Recently, the usage of stepped spillways, as energy dissipaters, has increased and led to a reduction in the size of the stilling basin. Extensive experimental considerations, plus the high cost and extended time required for laboratory methods, are among the major issues that require precise attention to determine optimal step design. This research deals with comparing the 2-D numerical simulation and experimental description in stepped spillways equipped with inclined steps and end sill together and presents a brisk, reliable, low-cost, and non-experimental approach to designing the steps. In this new type and complicated geometry, simulation is more complicated than horizontal steps, because it needs more accuracy around the end sills. The VOF Method and the k-ε standard turbulence model are proposed to simulate the flow pattern and evaluate the energy loss over stepped spillway. Energy dissipations obtained through the numerical approach have been compared with laboratory measurements and demonstrate reasonable agreement. Also, the flow pattern, velocity vectors and flow direction resulted from numerical simulation is in a good agreement with the experimental results.